Performance analysis of PHY layer for RIS-assisted wireless communication systems with retransmission protocols - Sheng Hao; Huyin Zhang (Journal of King Saud University: Computer and Information Sciences)
Reconfigurable intelligent surface (RIS) is one of the most promising technologies for constructing sixth-generation (6G) wireless networks. It has the capability of controlling the electromagnetic response, thereby improving the communication performance. Current studies about physical (PHY) layer analysis of RIS assisted WLC systems neglect the influence of retransmission protocols. Furthermore, the impacts of traffic rate and limited transit buffer on packet transmission and energy consumption are not considered for RIS assisted WLC systems. Focusing on the above problems, we put forward an insightful model to analyze the PHY layer performance of RIS assisted WLC systems using retransmission protocols. In the modeling process, we firstly provide an E2E (end to end) transmission model for the RIS assisted WLC system. The influence of typical retransmission protocols, containing ARQ (automatic repeat request) and hybrid ARQ (HARQ), channel fading types, frame duration on data transmission are comprehensively taken into consideration. Then, we establish an accurate energy consumption model through analyzing the queueing state of the transmitter with finite buffer size and traffic rate. Based on the above two models, we derive the closed-form expressions of PHY layer metrics for RIS assisted WLC systems considering the impact of retransmission protocols. In addition, we also analyze the bound performance of coverage range and expected power efficiency of RIS assisted WLC system with retransmission protocols. Finally, we evaluate the performance of RIS assisted WLC systems under different retransmission protocols and system parameters, and verify the proposed theoretical model.